Results and analysis of the Earth’s tidal observations in the territory of Ukraine - A. M. Kutniy; V.G. Pavlik; V.G. Bulatsen; V. Golubitsky; I. Bogdan; P.S. Korba; T. Babich; V. Plis (Геофизический журнал, 2015)
1300 monthly series of continuous tiltmeter and gravimetric observations have been processed on 25 earth tide stations of Ukraine. High-precision regional parameters  and  of the main tidal waves, Love’s numbers  and , differences of amplitude factors of diurnal tidal waves O1 and K1 have been  received, which characterize the real physical properties and condition of the Earth’s core and promote a choice or construction of its most reliable model.